SHALL I COMPARE THEE TO A...ROBOT?' THE USE OF CREATIVE ARTS AND SOCIAL ROBOTICS WITH OLDER ADULTS. (11th November 2018) - Fields, N; Xu, L; Greer, J; Doelling, K
Abstract: Research suggests that creative engagement in later life has a positive effect on mood in older adults. Research has also utilized social robots to address the psychosocial needs of older adults. However, few studies have linked participatory arts (e.g. theatre) as the creative engagement activity using a social robotic platform with older adults. An interdisciplinary team designed and implemented an intervention integrating theater and social robotics with the aim of improving the mood of study participants. A purposive sample of older adults age 65 and older (N = 8) participated in this pilot study. Participants completed 3 sessions of the Shakespearean theatre and social robotics intervention using the robot, Nao. Mixed methods included interview questions as well as short survey measures of depression, loneliness, and a simplified face scale for mood pre and post intervention. Results from the Wilcoxon Signed Ranks Tests suggested that the overall level of depression of the participants was reduced significantly after session 1 (z = -2.33, p < .05), after session 2 (z = -2.04, p < .05), and after session 3 (z = -2.00, p < .05). Scores on the loneliness and the simplified face scale also decreased after the three sessions, however, the changes were not statistically significant. Qualitative findings suggest that participants were highly engaged, comfortable, and receptive to the intervention. We discuss the promising aspects and limitations of this innovative study, the utility of social robotics for providing artistic engagement for older adults, and implications for interdisciplinary practice.